Clinical-histopathological correlation in acute appendicitis - Santiago, Pablo; Barberousse, Carlos; Lista, Ricardo (Cirugía del Uruguay, 1999)
There was rea/ized a prospective study of al/ patients and was established presurgery clinic diagnosis of acute appendicitis. The same study took place in Emergency Service of Maciel Hospital in Montevideo, during a period of six months (july-dec 1996).